2021
DOI: 10.1186/s12935-021-01762-w
|View full text |Cite|
|
Sign up to set email alerts
|

Three novel circRNAs upregulated in tissue and plasma from hepatocellular carcinoma patients and their regulatory network

Abstract: Background The regulatory roles of circular RNAs (circRNAs) in tumorigenesis have attracted increasing attention. However, novel circRNAs with the potential to be used as serum/plasma biomarkers and their regulatory mechanism in the pathogenesis of hepatocellular carcinoma (HCC) remain explored. Methods CircRNA expression profiles of tumor tissues and plasma samples from HCC patients were compiled and jointly analyzed. CircRNA–miRNA–mRNA interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Further experiments proved that circ-0004277 could promote EMT of HCC. Wang et al [ 10 ] identified hsa_circ_0009910, hsa_circ_0049783, and hsa_circ_0089172 were significantly upregulated in HCC tissues, which revealed that circRNAs was a potentially effective target for the treatment of HCC. Recently, Sun et al’s study [ 11 ] showed that hsa_circ_0008583 is highly expressed in HCC tissues, but its role and mechanism in the development of HCC has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments proved that circ-0004277 could promote EMT of HCC. Wang et al [ 10 ] identified hsa_circ_0009910, hsa_circ_0049783, and hsa_circ_0089172 were significantly upregulated in HCC tissues, which revealed that circRNAs was a potentially effective target for the treatment of HCC. Recently, Sun et al’s study [ 11 ] showed that hsa_circ_0008583 is highly expressed in HCC tissues, but its role and mechanism in the development of HCC has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…According to Wang’s research ( Wang L. et al, 2021 ), miR-18a-3p levels increased in HCC tissues. However, the mechanism of miR-18a-3p in liver cancer still remains elusive.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have shown that the expression of hsa-miR-144-3p in hepatocellular carcinoma is signi cantly higher than that in adjacent tissues, and the ratio of HSA144-3p/hsA-miR-21-5p increases signi cantly during the occurrence of hepatocellular carcinoma, which is even better than alpha-fetoprotein in ROC curve analysis, suggesting that HSA144-3p may be an excellent predictive marker of liver cancer (14). In addition, HSA-miR-455-5p has also been proved to be involved in the occurrence and development of liver cancer (15). Further analysis of Starbase showed that the expression of the four miRNAs was negatively correlated with the expression of VCAN in HCC (Figgure 8B).…”
Section: Vcan Mrna Expression Is Positively Correlated With Dnmt'smentioning
confidence: 98%